Dopamine agonist-induced penile erection and yawning: A comparative study in outbred Roman high- and low-avoidance rats - Sanna, Fabrizio; Corda, Maria Giuseppa; Melis, Maria Rosaria; Piludu, Maria Antonietta; Löber, Stefan; Hübner, Harald; Gmeiner, Peter; Argiolas, Antonio; Giorgi, Osvaldo (Pharmacology Biochemistry and Behavior, 2013)
The effects on penile erection and yawning of subcutaneous (SC) injections of the mixed dopamine D1/D2-like agonist apomorphine (0.02-0.2 mg/kg) were studied in outbred Roman high- (RHA) and low-avoidance (RLA) male rats, two lines selectively bred for their respectively rapid versus poor acquisition of the active avoidance response in the shuttle-box, and compared with the effects observed in male Sprague-Dawley (SD) rats. Apomorphine dose-response curves were bell-shaped in all rat lines/strains. Notably, more penile erections and yawns were recorded mainly in the ascending part of these curves (e.g., apomorphine 0.02-0.08 mg/kg) in both RLA and RHA rats compared to SD rats, with RLA rats showing the higher response (especially for yawning) with respect to RHA rats. Similar results were found with PD-168,077 (0.02-0.2 mg/kg SC), a D4 receptor agonist, which induced penile erection but not yawning. In all rat lines/strains, apomorphine responses were markedly reduced by the D2 antagonist L-741,626, but not by the D3 antagonist, SB277011A, whereas the D4 antagonists L-745,870 and FAUC213 elicited a partial, yet statistically significant, inhibitory effect. In contrast, the pro-erectile effect of PD-168,077 was completely abolished by L-745,870 and FAUC213, as expected. The present study confirms and extends previously reported differences in dopamine transmission between RLA and RHA rats and between the SD strain and the Roman lines. Moreover, it confirms previous studies supporting the view that dopamine receptors of the D2 subtype play a predominant role in the pro-yawning and pro-erectile effect of apomorphine, and that the selective stimulation of D4 receptors induces penile erection. © 2013 Elsevier Inc. All rights reserved.